A Cross-National Comparison of Myalgic Encephalomyelitis and Chronic Fatigue Syndrome at Tertiary Care Settings from the US and Spain - Bhatia, Shaun; Olczyk, Nicole; Jason, Leonard A.; Alegre, Jose; Llanos, Judith Fuentes-; Marrero, Jesus Castro- (American Journal of Social Sciences and Humanities, 2019)
Cross-national comparative studies are useful for describing the unique characteristics of complex illnesses, and can reveal culture-specific traits of disease frequency/severity and healthcare. Though myalgic encephalomyelitis (ME) and chronic fatigue syndrome (CFS) are debilitating conditions found all over the world, few studies have examined their characteristics across different countries. The purpose of this study was to compare the levels of functional impairment and symptomatology in patients with ME and CFS at tertiary referral hospitals in the US and Spain. Four hundred twenty potentially eligible participants (N = 235 from the US and N = 185 from Spain) who met the 1994 Fukuda et al. definition for CFS were enrolled. Both samples completed the medical outcomes study 36-item short-form health survey (SF-36) as a proxy for impairment, and the DePaul Symptom Questionnaire (DSQ) for patient symptomatology. ANCOVA and, where appropriate, MANCOVA tests were used to compare the SF-36 and DSQ items for illness characteristics between the samples. The patients from Spain demonstrated significantly worse functioning than those from the US in the SF-36 domains of physical functioning, bodily pain, general health functioning, role emotional, and mental health functioning. The Spanish sample also was also more symptomatic across all the DSQ-items, most significantly in the pain and neuroendocrine domains. These findings may be due to differences between the US and Spain regarding disability policy, perception of ME and CFS, and access to specialist care.